1983
DOI: 10.5479/si.19436696.391.1
|View full text |Cite
|
Sign up to set email alerts
|

The Caridean Shrimps (Crustacea--Decapoda) of the Albatross Philippine Expedition, 1907-1910

Abstract: SERIES PUBLICATIONS OF THE SMITHSONIAN INSTITUTION Emphasis upon publication as a means of "diffusing knowledge" was expressed by the first Secretary of the Smithsonian. In his formal plan for the Institution, Joseph Henry outlined a program that included the following statement: "It is proposed to publish a series of reports, giving an account of the new discoveries in science, and of the changes made from year to year in all branches of knowledge." This theme of basic research has been adhered to through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
232
1
12

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(257 citation statements)
references
References 2 publications
12
232
1
12
Order By: Relevance
“…The freshwater shrimps of the Philippine Archipelago have been studied by several authors (DANA 1852;COWLES 1914;BLANCO 1935BLANCO , 1939HOLTHUIS 1950HOLTHUIS , 1978JOHN-SON 1962;BALETE & HOLTHUIS 1992;CHACE & BRUCE 1993;CHACE 1997;SKET 1997). Up to present, 34 species of freshwater caridean shrimps were reported from the Philippines.…”
Section: Introductionmentioning
confidence: 99%
“…The freshwater shrimps of the Philippine Archipelago have been studied by several authors (DANA 1852;COWLES 1914;BLANCO 1935BLANCO , 1939HOLTHUIS 1950HOLTHUIS , 1978JOHN-SON 1962;BALETE & HOLTHUIS 1992;CHACE & BRUCE 1993;CHACE 1997;SKET 1997). Up to present, 34 species of freshwater caridean shrimps were reported from the Philippines.…”
Section: Introductionmentioning
confidence: 99%
“…Adults of the genus Ambidexter have a peculiar character, whereas other members of the family Processidae have only one pereiopod 1 chelate (usually the right) and the other with a simple dactyl, the species of Ambidexter have both pereiopods 1 symmetrically chelate (Chace 1997). This may well represent the ancestral condition in the Processidae (Williamson 1980).…”
Section: Discussionmentioning
confidence: 98%
“…According to our observations, these genera cannot be separated based on their larval morphology (Table 1). In addition, the adults are extremely similar and can be differentiated only by the absence (Processa) or presence (Nikoides) of exopods in pereiopod 1 (Manning and Chace 1971;Chace 1997). Despite the morphological resemblance of both adults and larvae in Processa and Nikoides, the molecular phylogeny of Caridea proposed by Bracken et al (2009) showed Processa as a sister group of Ambidexter, and Nikoides fell outside this group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarks: Chace, Jr. (1986) considered the differences of this species in comparison with the other members of the genus Acanthephyra as so important that he set up the new genus Heterogenys with the only species Heterogenys microphthalma. The identification of the species is easy because of several characteristic features.…”
Section: Mm)mentioning
confidence: 99%